The Effects of Integrative Reminiscence Therapy on Signs and Symptoms of Depression in the Elderly - Asghar Mohammadzadeh; Behrooz Dolatshahy; Parvaneh Mohammadkhani (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The Main aim of this study was to determine the effects of integrative reminiscence therapy on signs and symptoms of depression in the institutionalized elderly. Methods & Materials: This study was an experimental study with pre-test and post-test along with control group. The statistical society in this study consisted of all elderly adults residing in centers of Isfahan. Sample selection style was simple random sampling. The Geriatric Depression Scale (GDS) and Mini Mental Status Examination (MMSE) were primarily administered and the scores of higher than ten in GDS (severe and moderate depression) and higher than twenty one in MMSE were identified and a number of 36 subjects were randomly selected and were randomly divided into two groups, 18 participants to experiment group and 18 participants to the control group. Results: The analysis of the results was performed using independent t-test and chisquare. Mean of the difference of pretest and posttest results was acquired in experimental group (M=2.5385, SD=0.87706)and control group (M=1, SD=0.93541). Conclusion: The results of this study suggest that integrative reminiscence therapy can significantly result in reducing depression signs and symptoms in older adults. This intervention can serve as a supplementary treatment along with pharmaceutical treatment.